Oxygen uptake on-kinetics during six-minute walk test predicts short-term outcomes after off-pump coronary artery bypass surgery. Issue 5 (27th February 2019) - Rocco, Isadora Salvador; Viceconte, Marcela; Pauletti, Hayanne Osiro; Matos-Garcia, Bruna Caroline; Marcondi, Natasha Oliveira; Bublitz, Caroline; Bolzan, Douglas William; Moreira, Rita Simone Lopes; Reis, Michel Silva; Hossne, Nelson Américo; Gomes, Walter José; Arena, Ross; et al.
Abstract: Purpose: We aimed to investigate the ability of oxygen uptake kinetics to predict short-term outcomes after off-pump coronary artery bypass grafting. Methods: Fifty-two patients aged 60.9 ± 7.8 years waiting for off-pump coronary artery bypass surgery were evaluated. The 6-min walk test distance was performed pre-operatively, while simultaneously using a portable cardiopulmonary testing device. The transition of oxygen uptake kinetics from rest to exercise was recorded to calculate oxygen uptake kinetics fitting a monoexponential regression model. Oxygen uptake at steady state, constant time, and mean response time corrected by work rate were analysed. Short-term clinical outcomes were evaluated during the early post-operative of off-pump coronary artery bypass surgery. Results: Multivariate analysis showed body mass index, surgery time, and mean response time corrected by work rate as independent predictors for short-term outcomes. The optimal mean response time corrected by work rate cut-off to estimate short-term clinical outcomes was 1.51 × 10 −3 min 2 /ml. Patients with slower mean response time corrected by work rate demonstrated higher rates of hypertension, diabetes, EuroSCOREII, left ventricular dysfunction, and impaired 6-min walk test parameters. The per cent-predicted distance threshold of 66% in the pre-operative was associated with delayed oxygen uptake kinetics. Conclusions: Pre-operative oxygen uptake kinetics during 6-min walk test predicts short-term clinical outcomes after off-pump coronary artery bypass surgery. From a clinically applicable perspective, a threshold of 66% of pre-operative predicted 6-min walk test distance indicated slower kinetics, which leads to longer intensive care unit and post-surgery hospital length of stay. Implications for rehabilitation: Coronary artery bypass grafting is a treatment aimed to improve expectancy of life and prevent disability due to the disease progression; The use of pre-operative submaximal functional capacity test enabled the identification of patients with high risk of complications, where patients with delayed oxygen uptake kinetics exhibited worse short-term outcomes; Our findings suggest the importance of the rehabilitation in the pre-operative in order to "pre-habilitate" the patients to the surgical procedure; Faster oxygen uptake on-kinetics could be achieved by improving the oxidative capacity of muscles and cardiovascular conditioning through rehabilitation, adding better results following cardiac surgery. Trial registration: ClinicalTrials.gov identifier: NCT02758600.